-5x-12=-4x-14

Simple and best practice solution for -5x-12=-4x-14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5x-12=-4x-14 equation:


Simplifying
-5x + -12 = -4x + -14

Reorder the terms:
-12 + -5x = -4x + -14

Reorder the terms:
-12 + -5x = -14 + -4x

Solving
-12 + -5x = -14 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
-12 + -5x + 4x = -14 + -4x + 4x

Combine like terms: -5x + 4x = -1x
-12 + -1x = -14 + -4x + 4x

Combine like terms: -4x + 4x = 0
-12 + -1x = -14 + 0
-12 + -1x = -14

Add '12' to each side of the equation.
-12 + 12 + -1x = -14 + 12

Combine like terms: -12 + 12 = 0
0 + -1x = -14 + 12
-1x = -14 + 12

Combine like terms: -14 + 12 = -2
-1x = -2

Divide each side by '-1'.
x = 2

Simplifying
x = 2

See similar equations:

| 5[2h-3]=-3h+11 | | 22x+240=150-4x | | 2.5x-4=y | | (2x-7)+(4x+13)=90 | | 2x^2+12x-320=0 | | 4x+42=8x | | 18w+4=-36 | | x^2+x=-6 | | 30n+n=1440 | | 4[5x+7-8x]+2=-8 | | 5-3x=2x+30 | | 8.2(s+4)+6.7s=5.2 | | 5(12p+4)=-13p+4 | | 7(x+6)+6(x+6)=5x-5 | | 15-3(y-1)=7 | | 4x-3=4x-6 | | 5x-4=2x+46 | | 29-(-10)x=-18x+91 | | 2x-y+3z=-5 | | 5(x+14)=7x-26 | | -x-(-1)+5=-10-3x | | 3+2p=35 | | 9x-5=6x+49 | | 22x+70=17x+-95 | | -1+3a=3a+4 | | 24=2y+8 | | -3a+5=-16 | | 5x+3y=-5 | | P(x)=-16+368x-2035 | | 4+8m-1=7m+31-3m | | 4-1x=10 | | 5x^4+15x^3+20= |

Equations solver categories